Biological Characteristics of HLA-G and Its Role in Solid Organ Transplantation - Liu, Siqi; Bos, Nicolaas A.; Verschuuren, Erik A. M.; van Baarle, Debbie; Westra, Johanna (Frontiers in Immunology, 2022)
Organ transplantation is a lifesaving option for patients with advanced diseases. Rejection is regarded as one of the most severe risk factors post-transplantation. A molecule that contributes to immune tolerance and resisting rejection is human leukocyte antigen (HLA)-G, which belongs to the non-classical major histocompatibility complex class (MHC) I family. HLA-G was originally found to play a role during pregnancy to maintain immune tolerance between mother and child. It is expressed in the placenta and detected in several body fluids as soluble factor as well as different membrane isoforms on cells. Recent findings on HLA-G show that it can also play multifaceted roles during transplantation. This review will explain the general characteristics and biological function of HLA-G and summarize the views supporting the tolerogenic and other roles of HLA-G to better understand its role in solid organ transplantation (SOT) and its complications. Finally, we will discuss potential future research on the role of HLA-G in prevention, diagnosis, and treatment in SOT.